2011
DOI: 10.1016/s1470-2045(10)70290-4
|View full text |Cite
|
Sign up to set email alerts
|

Parotid-sparing intensity modulated versus conventional radiotherapy in head and neck cancer (PARSPORT): a phase 3 multicentre randomised controlled trial

Abstract: SummaryBackgroundXerostomia is the most common late side-effect of radiotherapy to the head and neck. Compared with conventional radiotherapy, intensity-modulated radiotherapy (IMRT) can reduce irradiation of the parotid glands. We assessed the hypothesis that parotid-sparing IMRT reduces the incidence of severe xerostomia.MethodsWe undertook a randomised controlled trial between Jan 21, 2003, and Dec 7, 2007, that compared conventional radiotherapy (control) with parotid-sparing IMRT. We randomly assigned pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

33
1,026
8
41

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,473 publications
(1,149 citation statements)
references
References 37 publications
33
1,026
8
41
Order By: Relevance
“…IMRT has been shown to benefit patients in the head and neck, 3 , 4 , 5 with the PARSPORT trial (Institute of Cancer Research, London, UK) demonstrating reduced incidence of xerostomia in patients treated with parotid‐sparing IMRT relative to those treated with conformal radiotherapy (6) . However, in order to realize the benefits afforded by IMRT, accurate delineation of targets and normal structures is essential (7) …”
Section: Introductionmentioning
confidence: 99%
“…IMRT has been shown to benefit patients in the head and neck, 3 , 4 , 5 with the PARSPORT trial (Institute of Cancer Research, London, UK) demonstrating reduced incidence of xerostomia in patients treated with parotid‐sparing IMRT relative to those treated with conformal radiotherapy (6) . However, in order to realize the benefits afforded by IMRT, accurate delineation of targets and normal structures is essential (7) …”
Section: Introductionmentioning
confidence: 99%
“…Particularly, radiation‐induced xerostomia is one of the most commonly reported long‐term side effects of radiation therapy for head and neck cancers. Intensity‐modulated radiation therapy (IMRT) can spare the major salivary glands and aid saliva flow recovery (6) . Kan et al (7) assessed the dosimetric impact of using AXB instead of AAA for the treatment of nasopharyngeal carcinoma with IMRT using a 6 MV photon beam.…”
Section: Introductionmentioning
confidence: 99%
“…Highly conformal radiation allows for a high dose to high‐risk areas, whilst sparing adjacent organs at risk (OAR) such as the parotid glands. Clinical studies have shown that IMRT reduces grade‐3 xerostomia in comparison to three‐dimensional conformal radiotherapy (3D CRT) 4 , 5 . For that reason, IMRT has become the standard treatment in many centers.…”
Section: Introductionmentioning
confidence: 99%